The Future of Harmful Algal Blooms in Florida Inland and Coastal Waters - Karl Havens (EDIS)
Microscopic algae in oceans and inland waters sometimes grow to excessive levels called “blooms.” Warmer water temperatures and increased nutrient levels exacerbate blooms, and when nutrients are high, temperature increases of just a few degrees cause exponential increases of algae and blooms. This 4-page fact sheet written by Karl Havens and published by the Florida Sea Grant College Program and UF/IFAS Extension explains why algal blooms can be harmful and provides advice for communities seeking to reduce nutrient levels in their lakes, streams, and other bodies of water. In a warmer future, harmful algal blooms will be much more challenging to control than they are today. http://edis.ifas.ufl.edu/sg153